Utilization of Mushroom Waste Fermentation (baglog) as a Growing Media for Silkworms (Tubifex sp.) Using a Recirculation System - Ilham Ikhsanul Putra; Niken Ayu Pamukas; Iskandar Putra (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
This research was carried out from November 20 2020 to January 10 2021 at the Laboratory of Aquaculture Technology and Seedling Unit Department of Aquaculture, Faculty of Fisheries and Marine Affairs, Riau University. This study aims to determine the effect of the use of oyster mushroom cultivation waste mixed with rice field mud on biomass and silkworm populations. The method used was Completely Randomized Design (CRD) with 4 treatment levels ; P1 (450 grams), P2 (550 grams), P3 (650 grams) and P4 (750 grams). Silkworm rearing media in this study was oyster mushroom waste (Baglog) which had been fermented using EM4. The parameters measured in this study were the growth of silkworm biomass, silkworm population and water quality. The results showed that the dose of oyster mushroom cultivation waste as a medium for rearing silkworms had a significant effect (P<0.05) on the growth of biomass and silkworm population. Treatment of oyster mushroom waste at a dose of 650 gram resulted in the growth of silkworm biomass of 59.33 grams/cm3 and a silkworm population of 100.943 ind/m2. The water quality parameters in the silkworm rearing tank were temperature 25,5-30oC, pH 6,1-7,6, DO 3,9-7,0 mg/L and ammonia 0,03-0,27 mg/L.